Review of the Neotropical blackfly subgenus Inaequalium Coscarón & Wygodzinsky (Diptera: Simuliidae) based on adults and pupal morphology - Hernández, Luis Miguel; Shelley, Anthony John; de Luna Dias, Antonio Paulino Andrade; Maia-Herzog, Marilza (Zootaxa, 2007)
The species of the subgenus Inaequalium are reviewed based on adult and pupal morphology. All main taxonomic characters are fully illustrated together with a key to pupae for species identification. Discussions on the species’ taxonomy and brief summaries of their distribution and biology are also provided. As a result of this study, 14 species are now included in the subgenus Inaequalium. They are placed into two species groups, the botulibranchium species group with three species and the inaequale species group with 11 species, including two that are treated as species inquirendae: S. lurybayae Smart and S. parimaense Ramírez-Pérez, Yarzábal, Takaoka, Tada & Ramírez. Simulium lurybayae Smart, S. margaritatum Pepinelli, Hamada & Luz and S. maranguapense (Pessoa, Ríos-Velásquez & Py-Daniel) are now placed in the inaequale species group. Two lectotypes are designated for the following species: S. clavibranchium Lutz and S. diversibranchium Lutz. Simulium hauseri (Coscarón & Coscarón-Arias) is regarded as an unavailable name.